Factors affecting two-point discrimination in Argus II patients - Yücel, Ezgi I.; Sadeghi, Roksana; Kartha, Arathy; Montezuma, Sandra Rocio; Dagnelie, Gislin; Rokem, Ariel; Boynton, Geoffrey M.; Fine, Ione; Beyeler, Michael (Frontiers in Neuroscience, 2022)
Two of the main obstacles to the development of epiretinal prosthesis technology are electrodes that require current amplitudes above safety limits to reliably elicit percepts, and a failure to consistently elicit pattern vision. Here, we explored the causes of high thresholds and poor spatial resolution within the Argus II epiretinal implant. We measured current amplitude thresholds and two-point discrimination performance (the ability to determine whether one or two electrodes had been stimulated) in 3 blind participants implanted with Argus II devices. Our data and simulations show that axonal stimulation, and lift and retinal damage all play a role in reducing performance in the Argus 2, by either limiting sensitivity or reducing spatial resolution. Understanding the relative role of these various factors in reducing prosthetic sensitivity and resolution will be critical for developing and surgically implanting devices that can successfully subserve pattern vision.